Ninguém nasce racista: o discurso de combate ao racismo no programa Criança Esperança 2016 - Campos, Monahyr Gonçalves (2018)
This paper NOBODY IS BORN A RACIST: THE DISCOURSE OF FIGHT RACISM IN THE TV PROGRAM CRIANÇA ESPERANÇA (CHILD HOPE) - 2016, is set within the Project “Discourse in Scenes”, of the Research Line “Text, Discourse and Teaching: reading processes and written and spoken text production” of Cruzeiro do Sul University. In order to carry out this study, the short-film “Nobody is born a racist. Remain a child” (directed by Chico Gomes & Pedro Mosca; produced by Rafael Dragaud. Bossa Nova Films. Criança Esperança. Rede Globo-Unesco. 2016. 3:44 minutes) was analysed, having as a basis the concepts of contextualization, discursive and ideological formation presented by Orlandi (2003). The general objective of this work is to analyze the fight racism discourse in the film; as specific objective this work intends to analyze the Enunciation Scenes in the film, most specifically Scenography, the discursive intentions and pathemisation resources in order to find out traces of emotion in the discourse The short film was produced by Globo Broadcasting for the TV program “Criança Esperança” 2016, annual show which counts on the support of UNICEF, declared as a TV program aimed at fighting racism. This research is based on French Discourse Analysis, especially on the concept of Scene Enunciation, and at a greater length Scenography, developed by Maingueneau (2002), still under the precepts of Discursive Intentions, primarily its discursive expectations as well as Pathemisation, presented by Charaudeau (2004, 2010a, 2010b, 2015). This analysis is also supported on the perception of how the presence of black people in the media occurs and on the relation between Racism and Discourse, based on Silva and Rosemberg (2015). By the end of the analysis, we verified that the video was created as a marketing strategy aimed at capturing and seducing the audience without discussing it with the people who are most interested in the racism theme, that is to say, the black people community.